2017
DOI: 10.1063/1.4977910
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Brillouin and Raman scattering by alternating-polarization light

Abstract: A new method to reduce the scattering levels of stimulated Raman scattering (SRS) and stimulated Brillouin (SBS) scattering is proposed using alternating-polarization light. The effect of the new technique is related to the alternating time. If the alternating time is smaller than the growth time, the scattering level of SRS or SBS can be decreased. The SBS process is simulated by the fluid method, and the SRS process is verified by the particle-in-cell method. This method is also compared with the spike train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…[26] All these methods or combinations of them have been widely used to control the peak intensities of laser spatial speckles and hence to suppress instabilities in ICF, but they cannot reduce LPIs to a tolerable level. [27,28] Recently, some new theoretical schemes for suppressing LPIs by changing lasers have also been proposed, including various broadband technologies, [29][30][31][32] two-color incident light, [33][34][35] spike trains of uneven duration and delay (STUD), [36][37][38][39] rotating polarization, [40][41][42] alternating polarization, [43,44] the discretely changing phase, [45] etc. It can be seen that in order to reduce the development of LPIs, existing schemes focus on changing the laser frequency, amplitude, polarization direction and phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] All these methods or combinations of them have been widely used to control the peak intensities of laser spatial speckles and hence to suppress instabilities in ICF, but they cannot reduce LPIs to a tolerable level. [27,28] Recently, some new theoretical schemes for suppressing LPIs by changing lasers have also been proposed, including various broadband technologies, [29][30][31][32] two-color incident light, [33][34][35] spike trains of uneven duration and delay (STUD), [36][37][38][39] rotating polarization, [40][41][42] alternating polarization, [43,44] the discretely changing phase, [45] etc. It can be seen that in order to reduce the development of LPIs, existing schemes focus on changing the laser frequency, amplitude, polarization direction and phase.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39] Liu et al reported the reduction of alternating-polarization light on the scattering levels of SRS and SBS, and the scattering level could be dramatically decreased by more than one order of magnitude under proper alternating-polarization parameters. [43] Yang et al proposed a method in which the phase of incident light was discretely changed. It was shown that the method could broaden the light spectrum and detune the three-wave coupling process; the reflectivity of SRS was observed to decrease significantly.…”
Section: Introductionmentioning
confidence: 99%
“…There are two mechanisms mainly proposed up to date. One is to optimize the uniformity of the incident laser spot such as spatial smoothing, spectral dispersion [10] and polarization smoothing, [11,12] the other is to decrease the interaction length of SBS such as the spike trains of uneven duration and delay (STUD), [13] alternating-polarization light, [14] polarization rotation [15] and two perpendicular linear polarization. [16] In this article, polarization rotation and two perpendicular linear polarizations are performed to suppress the absolute growth of auto-resonant stimulated Brillouin scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and numerical works were also performed [6][7][8][9]. To control the laser plasma interactions, many methods were put forward from the points of laser parameters and plasma parameters, such as laser smoothing technology [10], the spike train of uneven duration and delay [11][12][13][14], the alternating polarization [15], the multi-color light incident [16], changing the gas density in holhraum [17] and increasing the electron temperature. While these methods were considered with the un-magnetized plasma.…”
Section: Introductionmentioning
confidence: 99%